Falling behavior and control effect on temperature rise under heating condition concerning water film flow on steel shutter surface - Yoshifumi Ohmiya; Manabu Tange; Kohji Nakamura; Yuya Miyazawa (Japan Architectural Review)
Abstract A series of experiments were carried out on water film flow formed by a water discharge system on the surface of steel shutters. The experiments used three types of steel shutters for fire protection. The rates for water Ws supplied to the steel shutter from the slit of the water discharge system was changed. First, the water film flow that formed on the convex surfaces of the main curved parts of connected shutter slats was observed under non‐heating conditions. Then, the velocity of water film flow on the surface of steel shutter was analyzed by direct cross‐correlation method using PIV system. Next, the temperature distribution and other parameters of the water film flow were investigated under heating conditions using a radiation panel. The heating condition was changed by adjusting the separation distance between the radiation panel and the test specimen. To measure the temperatures on the non‐heated side of the test specimen, K‐type thermocouples were used. Fundamental knowledge was obtained about the behavior of water film flow on steel shutter surfaces under non‐heating conditions as well as the thermal insulation and other effects of the water film under heating conditions.